NEUROPSYCHOLOGICAL PERFORMANCE IN A SAMPLE OF INSTITUTIONALIZED CHRONIC SCHIZOPHRENIC PATIENTS - Luis Maia (Cuadernos de Neuropsicologia, 2010)
We study the results of a descriptive and exploratory study, with the intent to understand the results of a 21 male schizophrenic patients interned in a Portuguese Mental Health Care Centre, evaluated with neuropsychological test. We tried also to link these tests with variables such as schooling, family contact or lengh of internment. The assessment instruments were: Digits Series and Vocabulary Task, both from WAIS, Raven Progressive Matrices, Rey’s Complex Figures, Luria’s Series Neuropsychological Screening, Clock Task - Neuropsychological Screening and Visual Search and Attention Test. Results show that there is not an attention deficit clinically significant, even that data suggests light attention affection; also variables like family contact and schooling appear as protective factors of memory and also seems to be important for the planning / organization functions.